Universal Data Logger System for Environmental Monitoring Applications - Osman Abd Allah; Mohammed Abdalla; Suliman Abdalla; Amin Babiker; Alaa Awad Allah (IAES Indonesian Section, 2017)
Collecting huge amount of data in long time acquisition systems like in environmental monitoring, there is a need to collect and save data over time for further use or analysis. A data logger is an electronic device that records data over time or in a relation to location either with a built-in instrument, sensor or via an external instruments and sensor. In this paper, a data logger system is designed to use as a stand-alone or computer based device. When used as a standalone system, all data acquired are saved in SD memory card, which must be copied and erased periodically depending on the memory size. When used as computer based device, all the data sent to the computer via the serial port and stored automatically in achieved files. The limit of those files size only restricted by the capacity of the disk. The data logger is designed using an Arduino UNO board and LabView software, and it has the flexibility to set it up for different user options. With this system, the user could be able to record and read back sensory data to or from existing files, or in automatically generated files and plot these readings in a graph. Also, the user have the ability to choose the periodic time at which a sample record in a file in term of seconds, minutes or hours. The system designed to monitor and record a single channel data, but it could be adapted to monitor more than one channel.